Factors Affecting Stock Prices : The Linkage between Stock Market and Product Market - Gupta, Rajnarayan (Indian Journal of Finance, 2012)
A wide number of investigations have been made to identify the factors determining stock prices. All those investigations are, however, based on the single equation technique, where explanatory variables are treated as exogenous. The present study formulates a simultaneous equation model to explore inter connections between the explanatory variables. The model links up stock market with the product market, and the proposed model is empirically verified for the Indian cement industry. Panel data have been considered for that purpose. Empirical results support the model and establish the linkage between the stock market and the product market.